1999
DOI: 10.1002/(sici)1097-4687(199907)241:1<61::aid-jmor4>3.3.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Development of dermal denticles in skates (Chondrichthyes, Batoidea): Patterning and cellular differentiation

Abstract: Patterning, cellular differentiation, and developmental sequences of dermal denticles (denticles) are described for the skate Leucoraja erinacea. Development of denticles proceeds caudo-rostrally in the tail and trunk. Once three rows of denticles form in the tail and trunk, denticles begin to appear in the region of the pelvic girdle, medio-caudal to the eyes and on the pectoral fins. Although timing of cellular differentiation of denticles differs among different locations of the body, cellular development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…We suggest that the 'patterned tail scale' module represents the more ancient, relative to the scattered body scales, which may be related to suggestions that the tail is itself an independent developmental unit relative to the rest of the body (reviewed in Handrigan 2003). Data on pattern regulation and histology of tail scales in other taxa, and the histology of bilaterally axially patterned scales on the body during early ontogeny, for example, in holocephalans (Didier 2004) and other elasmobranchs (Miyake et al 1999;Freitas & Cohn 2004) would test these hypotheses.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…We suggest that the 'patterned tail scale' module represents the more ancient, relative to the scattered body scales, which may be related to suggestions that the tail is itself an independent developmental unit relative to the rest of the body (reviewed in Handrigan 2003). Data on pattern regulation and histology of tail scales in other taxa, and the histology of bilaterally axially patterned scales on the body during early ontogeny, for example, in holocephalans (Didier 2004) and other elasmobranchs (Miyake et al 1999;Freitas & Cohn 2004) would test these hypotheses.…”
Section: Discussionmentioning
confidence: 59%
“…Miyake et al 1999;Didier 2004;Freitas & Cohn 2004;Eames et al 2007). This patterning is observed in bilateral scale rows along the body and rows associated with the lateral sensory canals; patterned scale rows have also been described in association with the tail fin (axial lobe).…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated by Miyake et al (1999), elasmobranchs (sharks, skates and rays) provide a promising system for comparing gene expression between dermal denticles, true teeth and oropharyngeal denticles. Another group of organisms with potential in this respect are ¢shes of the genus Polypterus, which possess odontodes on dermal bones, scales, ¢n spines and throughout the oropharyngeal region (Meinke 1982;Jollie 1984).…”
Section: Approaches To the Further Study Of Modularity And Dissociatimentioning
confidence: 99%
“…Despite the seemingly disorganized distribution of denticles in the skin of most adult elasmobranchs, the ontogenetically earliest denticles may be arranged in distinct rows at specific sites: on either side of the caudal fin axis in Heterodontus (Johanson et al, 2007), from the pectoral fins to the caudal peduncle in Scyliorhinus (Freitas and Cohn, 2004), and along both sides of the caudal peduncle in Cephaloscyllium and Squalus (Grover, 1974;Maisey, 1974). Thus, initial denticle patterning in elasmobranchs can be highly organized, but this transient stage can disappear secondarily; in skates, however, some of the first denticles to form in juveniles are arranged in rostrocaudal rows that are retained into adulthood (Grover, 1974;Miyake et al, 1999). It has been suggested that initial denticle patterning in Heterodontus is related to myomere pattern (Johanson et al, 2007), as with osteichthyan scales (Sire and Akimento, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike pigmentation patterns, which are related to the differential distribution of melanocyte cells, dermal denticles form de novo at the interface of the epidermis and dermis, on the basal lamina (e.g., Miyake et al, 1999;Barrio et al, 2009). Reaction-diffusion models that involve coupling between layers (Yang et al, 2002;Barrio et al, 2009;Madzvamuse et al, 2015) approximate the interaction of morphogens through the basal lamina between the epidermal and dermal layers.…”
Section: Introductionmentioning
confidence: 99%